Posted by **Liz** on Sunday, October 7, 2012 at 10:08pm.

find the equation for the line tangent to the curve at the given point.

(x^2)(y^2)-2xy+x=1 at (2, 1/2)

- calculus PLZ HELP!! -
**Reiny**, Sunday, October 7, 2012 at 10:22pm
(x^2)(2y)dy/dx + 2x(y^2) - 2xdy/dx - 2y +1 = 0

dy/dx(2x^2 y - 2x) = -2x y^2 + 2y - 1

dy/dx = (-2xy^2 + 2y - 1)/(2x^2y - 2x)

at (2, 1/2)

dy/dx = (-2(2)(1/4) + 2(1/2) - 1)/(2(4)(1/2) - 4)

= (-1 + 1 -1)/0

ahh ,we are dividing by zero, so the tangent must be a vertical line

since it passes through (2, 1/2) its equation must be

x = 2

## Answer This Question

## Related Questions

- calculus - Consider the curve defined by 2y^3+6X^2(y)- 12x^2 +6y=1 . a. Show ...
- Calculus 1 - Use implicit differentiation to find an equation of the tangent ...
- calculus - Use implicit differentiation to find an equation of the tangent line ...
- math calculus - Use implicit differentiation to find the equation of the tangent...
- Help Calc.! - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy)/(x^2+y^2+1...
- please help; calc - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy)/(x^2+...
- Calculus - the curve: (x)(y^2)-(x^3)(y)=6 (dy/dx)=(3(x^2)y-(y^2))/(2xy-(x^3)) a...
- calculus - find the equation of the tangent line at the given value of x on the ...
- Need help fast on calc - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy...
- Math, Calc - Use implicit differentiation to find an equation of the tangent ...

More Related Questions